PENGARUH AKSEPTABILITAS, AFORDABILITAS, AKSESIBILITAS TERHADAP KEPUTUSAN NASABAH PELAKU UMKM DALAM PEMBIAYAAN SYARIAH - Nurul Fatimah; Agung Abdullah (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2025)
This study aims to analyze the influence of acceptability, affordability, and accessibility on the decisions of MSME customers to use Sharia financing at BPRS Hikmah Khazanah in Joyotakan Village. The study employed a quantitative approach with a causal method, collecting data through a questionnaire from 150 respondents. The data were analyzed using multiple linear regression, following initial testing for validity, reliability, and classical model assumptions. The results showed that all three independent variables had a significant influence on customer decisions simultaneously. However, only affordability and accessibility had a positive and considerable influence, to some extent. Affordability was the dominant factor influencing decisions, followed by accessibility (ease of procedures and services). Meanwhile, acceptability (compliance with Sharia principles) showed to have a partial, non-significant effect. These findings suggest that the primary considerations of MSMEs are pragmatic, such as affordable costs and accessible services, rather than normative considerations of Sharia compliance. The implication of this research is the importance of BPRS to focus more on policies that simplify procedures, provide clear information, and offer competitive cost schemes to increase interest and decision-making on sharia financing among MSMEs. Keywords: Acceptability, affordability, accessibility, customer decision.